Interpretasi Praktik Akuntansi dari Perspektif Pengusaha Mikro - Dwinanda Adijaya Sasmita; Ghozy Kamal Hanif; Naufal Dzaky Arinata (Jur. Akuntansi, Politeknik Negeri Malang, 2019)
AbstractMicro and small entrepreneurs in their business practices have their own creativity in making financial records for transactions. The recording style in the financial records used has a hidden meaning. The art of accounting is different from what we understand. This study aims to determine the various phenomena and hidden meaning of accounting practices conducted by micro and small entrepreneurs. Informant for this research is owner of Mitra Shava Laundry in Malang. Data is collected through interview with informant and analysed by employing phenomenology.the results from this reserach to determine the interpretation of accounting practices where accounting itself has a lot of meanings. not only for the media to find benefits but also the meaning behind it. This research is finding the accounting from small and micro entrepreneur in the form of written and unwritten recording and the meaning of each recording.